Fibroadipogenic Progenitors Regulate the Basal Proliferation of Satellite Cells and Homeostasis of Pharyngeal Muscles via HGF Secretion - Kim, Eunhye; Wu, Fang; Lim, Danbi; Zeuthen, Christopher; Zhang, Yiming; Allen, James; Muraine, Laura; Trollet, Capucine; Vest, Katherine E.; Choo, Hyojung J. (Frontiers in Cell and Developmental Biology, 2022)
Skeletal muscle stem cells, known as satellite cells (SCs), are quiescent in normal adult limb muscles. Injury stimulates SC proliferation, differentiation, and fusion to regenerate muscle structure. In pharyngeal muscles, which are critical for swallowing foods and liquids, SCs proliferate and fuse in the absence of injury. It is unknown what factors drive increased basal activity of pharyngeal SCs. Here, we determined how niche factors influence the status of pharyngeal versus limb SCs. In vivo, a subset of pharyngeal SCs present features of activated SCs, including large cell size and increased mitochondrial content. In this study, we discovered that the pharyngeal muscle contains high levels of active hepatocyte growth factor (HGF), which is known to activate SCs in mice and humans. We found that fibroadipogenic progenitor cells (FAPs) are the major cell type providing HGF and are thus responsible for basal proliferation of SCs in pharyngeal muscles. Lastly, we confirmed the critical role of FAPs for pharyngeal muscle function and maintenance. This study gives new insights to explain the distinctive SC activity of pharyngeal muscles.